Aspek Klinis dan Pemeriksaan Laboratorium Sindrom Hiperimunoglobulin-M - Sihombing, Martina Rentauli (Universitas Kristen Krida Wacana, 2024)
Hyperimmunoglobulin-M Syndrome (HIGM) is a set of symptomps due to primary immunodeficiency characterized by low levels of immunoglobulin G (IgG), immunoglobulin A (IgA), immunoglobulin E (IgE), and normal or increased levels of immunoglobulin M (IgM) or recurrent infections. HIGM syndrome was initially thought to be caused by genetic defects related to the X chromosome only, but along with advances in molecular technology in detecting genetic abnormalities, other autosomal-type defects were found. Genetic defects in HIGM Syndrome cause disruption of the maturation process of humoral immunity, especially diversity through CSR, and increased affinity through SHM. Clinical manifestation of HIGM patients varies greatly and depends on the defect in the CD40L or CD40 signal pathway. Current therapy given for HIGM patients aim to resolve those clinical manifestation and fix the production of high-affinity antibody. Life expectancy of patients without a bone marrow transplant is estimated to be less than 30 years.